2015
DOI: 10.1590/s1984-29612015046
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii, Neospora caninum and Leishmania spp. serology and Leishmania spp. PCR in dogs from Pirassununga, SP

Abstract: We examined the presence of antibodies against the parasites Toxoplasma gondii, Neospora caninum, and Leishmania spp., as well the presence of DNA from Leishmania spp., in dogs from Pirassununga -SP. The seropositivity rate was compared with the animals' originating location. Three hundred seventy-three blood samples from the county's kennel and local veterinary clinics were collected and analyzed. A total of 300 samples were tested for T. gondii and N. caninum using an indirect immunofluorescence antibody tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…Surprisingly, to the best of our knowledge, this study was the first serosurvey on this dog population worldwide. Despite the outdoor and free-roaming habits of neighborhood dogs, which may increase their exposure to protozoan infections (AZEVEDO et al, 2005;COLLANTES-FERNÁNDEZ et al, 2008;MOURA et al, 2009;NAZIR et al, 2014), they presented in this study a low seroprevalence for T. gondii and N. caninum compared with literature results (MEIRELES et al, 2004;SEABRA et al, 2015;VALADAS et al, 2010), which may indicate that there was a situation of low environmental oocyst contamination (MEIRELES et al, 2004). Since dogs play a secondary role in the toxoplasmosis cycle, neighborhood dogs may be considered to be true environmental sentinels for T. gondii, particularly when sharing a contaminated urban environment and contaminated food and water (MEIRELES et al, 2004).…”
Section: Introductioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Surprisingly, to the best of our knowledge, this study was the first serosurvey on this dog population worldwide. Despite the outdoor and free-roaming habits of neighborhood dogs, which may increase their exposure to protozoan infections (AZEVEDO et al, 2005;COLLANTES-FERNÁNDEZ et al, 2008;MOURA et al, 2009;NAZIR et al, 2014), they presented in this study a low seroprevalence for T. gondii and N. caninum compared with literature results (MEIRELES et al, 2004;SEABRA et al, 2015;VALADAS et al, 2010), which may indicate that there was a situation of low environmental oocyst contamination (MEIRELES et al, 2004). Since dogs play a secondary role in the toxoplasmosis cycle, neighborhood dogs may be considered to be true environmental sentinels for T. gondii, particularly when sharing a contaminated urban environment and contaminated food and water (MEIRELES et al, 2004).…”
Section: Introductioncontrasting
confidence: 52%
“…For dogs living in stray situation in Brazil, as neighborhood dogs, the seroprevalence for Leishmania spp. have been ranging from 0.0027% to 32.5% (FREHSE et al, 2010;SEABRA et al, 2015;TRONCARELLI et al, 2009;VALADAS et al, 2010), for T. gondii from 31.6% to 68.4% (MEIRELES et al, 2004;SEABRA et al, 2015;SOUZA et al, 2003;VALADAS et al, 2010), for T. cruzi from 2.0% to 4.0% (MORAIS et al, 2013;TRONCARELLI et al, 2009) and for N. caninum from 3.2% to 22.1% (FRIDLUND-PLUGGE et al, 2008;SEABRA et al, 2015;SOUSA et al, 2012;VALADAS et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…may enhance the susceptibility of dogs to N. caninum infection (CRINGOLI et al, 2002). Serological surveys correlating N. caninum and Leishmania spp., had been conducted ANDREOTTI et al, 2006;GUIMARÃES et al, 2009;GRECA et al, 2010;VALADAS et al, 2010a;LOPES et al, 2011;PAULAN et al, 2013;SEABRA et al, 2015;CONSTANTINO et al, 2016). In dogs from endemic cities of visceral leishmaniosis such as Araçatuba, SP , Campo Grande, MS (ANDREOTTI et al, 2006), and Teresina, PI (LOPES et al, 2011), positive association was found (Table 3).…”
Section: Epidemiologymentioning
confidence: 92%
“…When dogs were tested in the city, only one was kDNA Leishmania spp. cPCR positive(Seabra et al, 2015). Herein, positive cats belong to a NGO, and life histories of these stray animals are unknown.Lutzomyia longipalpis is the most important L. infantum vector in Latin America endemic areas (Quinnel; Courtenay et al 2009).…”
mentioning
confidence: 99%